Stabilization of Discrete-Time Planar Switched Linear Systems with Impulse - Yanli Zhu; Yuangong Sun (Discrete Dynamics in Nature and Society)
We study the stabilization problem of discrete-time planar switched linear systems with impulse. When all subsystems are controllable, based on an explicit estimation on the state transition matrix, we establish a sufficient condition such that the switched impulsive system is stabilizable under arbitrary switching signal with given switching frequency. When there exists at least one uncontrollable subsystem, a sufficient condition is also given to guarantee the stabilization of the switched impulsive system under appropriate switching signal.